(3QSGdI aj bhGYO GdEYQGHs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde bhdg hCeG GdaJMI aJchf YdGeI ddNaV ai GdGSe GdPi dGjfUQa , EYde Cfg ENJda ai ETJbGbg gd gh ef GdUQa hgh GdNGdU ef GddHS s
(3BNQgG (B:s
(3bGd eDdag GfJgi eG EdJbWg hbjOg cGJHg eMeO GdSYjO YGe (B1268 (3JbQjHkG hJSgjdkG ddeSCdI GdJi cfJ CSJghdgG dfaSi hCHfGFi fMf CSQi HeOjfI CHfhGR YfO GdaQGfSjS OeQge Gddg , Bejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs